Trends in Assortative Mating and Offspring Outcomes - Bernt Bratsberg; Simen Markussen; Oddbjørn Raaum; Knut Røed; Ole J. Røgeberg (Institute of Labor Economics (IZA), 2018)
Fertility patterns and assortative mating help shape the level and the distribution of offspring outcomes. Increased assortative mating among the less educated has been reported across Western nations, suggesting that inequality in parental resources may be on the rise. In times of rising attainment, we argue that it is difficult to interpret trends in educational assortative mating as they can arise from change in sorting into education as much as from change in sorting into partnerships. Using rank measures of parental resources that have constant marginal distributions, we uncover evidence of declining assortative mating over the last 30 years in Norway. We also find an increasingly positive selection into parenthood. Estimating the contribution of parental resources to offspring outcomes, we show that recent trends in mating have caused a small rise in average offspring education and earnings as well as a decline in offspring inequality.
Keywords: J12; J24; J62; D63; 330; assortative mating; homogamy; intergenerational mobility; inequality